Analysis of Multi Stakeholder Initiatives (MSI) on Sustainability: analyzing the definition, governance structure and issues in RSPO, EITI, FSC, and MSC - WALI, MUHAMMAD YOUSEEB (2019)
In this research we have looked at the role of Multi Stakeholder Initiatives (MSI) on sustainability by specifically focusing on following MSIs; Roundtable on Sustainable Palm Oil (RSPO), Extractive Industries Transparency Initiative (EITI), Forest Stewardship Council (FSC) and Marine Stewardship Council (MSC). First, we have highlighted the principles of these MSIs, which tells about how they define sustainability, then we have highlighted the governance structure of these MSIs and identified the issues these MSIs face. After this we have compared the literature review with the principles, governance structure and issues in MSIs to find whether literature review is in line with our findings or not. Then we have identified the actions taken by these MSIs to address the issues that they face in order to find out whether MSIs work on identified issues and whether the governance structure plays a significant role in it or not. According to our findings, despite some differences in governance structure of MSIs the governance structure does not play major role in issues identified. MSIs do address the issues it faces as majority of the identified issues have been either resolved or new policies are being made to address them , however issues which are becoming beyond the control of MSIs, such as number of alternative certifications, socio political issues need attention as MSIs alone cannot deal with it.